2015
DOI: 10.5007/2175-7925.2015v28n2p137
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimentos e usos da fauna por caçadores no semiárido brasileiro: um estudo de caso no estado da Paraíba, Nordeste do Brasil

Abstract: Esse estudo foi realizado em uma comunidade tradicional no semiárido paraibano e registrou as principais espécies animais caçadas, avaliando as implicações conservacionistas desta prática. Um total de 24 entrevistados citou 78 espécies de vertebrados tetrápodes silvestres caçados na região. Esses animais podem ser organizados, de acordo com o uso, em dez categorias diferentes: zooterapia, etnoveterinária, uso cosmético, uso/interação místico-religiosa, criação/domesticação, comércio, uso/interação ornamental, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
3
13
0
2
Order By: Relevance
“…According to Marques (2001), human populations attribute importance to the species they know better and for which they have feelings and beliefs. In a study on the knowledge and use of fauna by hunters in the semiarid region of the state of Paraíba, Barbosa & Aguiar (2015) recorded different forms of use, such as medicinal (treatment of ailments), mystical-religious (inclusion of animals in rituals), as pets and as a food source. In another study conducted in the semiarid region of northeastern Brazil, Barbosa & Aguiar (2012) report that different species of fauna are used for mystical-religious purposes, such as amulets for the "evil-eye", sacrificial rituals, cures for spiritual illnesses and folk stories.…”
Section: Human Perceptionsmentioning
confidence: 99%
“…According to Marques (2001), human populations attribute importance to the species they know better and for which they have feelings and beliefs. In a study on the knowledge and use of fauna by hunters in the semiarid region of the state of Paraíba, Barbosa & Aguiar (2015) recorded different forms of use, such as medicinal (treatment of ailments), mystical-religious (inclusion of animals in rituals), as pets and as a food source. In another study conducted in the semiarid region of northeastern Brazil, Barbosa & Aguiar (2012) report that different species of fauna are used for mystical-religious purposes, such as amulets for the "evil-eye", sacrificial rituals, cures for spiritual illnesses and folk stories.…”
Section: Human Perceptionsmentioning
confidence: 99%
“…The majority of these works, nonetheless, are based in studies about traditional or indigenous populations (León andMontiel 2008, Santos-Fita et al 2012). In Brazil, despite of hunting being illegal, some studies have also demonstrated these varied nuances of hunting activities (Barbosa et al 2011, Barbosa and Aguiar 2015. Recently, a thorough study tried to analyze the multiple aspects of hunting in different biomes in the country (Fernandes-Ferreira 2014).…”
Section: Hunting Practices and Environmental Influencementioning
confidence: 99%
“…Malkin 1956a, b, 1958, Sturtevant 1964, Berlin et al 1973. Recently, however, the diversity of the aspects approached in the area is growing considerably, with researches that include zoological perception and classification (Posey 1982, myths and beliefs involving the animals (Lewis 1991, Léo Neto et al 2009, Barbosa and Aguiar 2012, sociobiological aspects of the use of fauna (Posey 1978, Dias et al 2011, Barbosa and Aguiar 2015, traditional medicine, cosmetic, ritualistic and nutritional aspects including animals (Costa-Neto and Oliveira 2000, Lev 2003, Alves and Pereira Filho 2007, Barboza et al 2007, Rosa et al 2011, domestication and management of faunistic resources (Haudricourt 1977, Digard 1992, the cognitive processes related to the management of fauna and the conservation of biodiversity (Fleck andHarder 2000, Alves andNishida 2002) and hunting and its impacts on animal populations (Balée 1985, Quijano Hernandez and Calme 2002, Souto 2007, e.g. Alves et al 2009a, b, c, 2012, Barbosa et al 2010, Bezerra et al 2012, Souza and Alves 2014, tending towards growth and expansion of the researches done in Brazil.…”
Section: Historical Aspects Of Ethnozoologymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the traditional use of mammals, a growing number of studies have been carried out in Brazil (e.g., [10–13]). In the Caatinga biome, some species of mammals have been used for food, pets, medicinal, magic/religious, artisanal, veterinary (folk medicine used in animals), and control (slaughter of wild animals that feed on domestic species) purposes (e.g., [14–19]). Animals that have utility value for the population are mostly killed in hunting activities, which, according to Chiarello et al [20], represent one of the greatest threats to wild mammals.…”
Section: Introductionmentioning
confidence: 99%